The Effect of Surface Acting on Job Stress and Cognitive Weariness Among Healthcare Workers During the COVID-19 Pandemic: Exploring the Role of Sense of Community - Sousan, Arman; Farmanesh, Panteha; Zargar, Pouya (Frontiers in Psychology, 2022)
Surface acting has been found as a heavy emotional and cognitive task practiced by nurses, which has negative consequences on their well-being. Shortage of nurses along with the occurrence of COVID-19 pandemic have worsen the situation. Based on Job Demands – Resources and Conservation of Resources theories, this study aims to investigate the adverse impact of practicing surface acting and buffering effect of sense of community on job stress and cognitive weariness among Iranian nurses confronting COVID-19. The current research is written within the scope of Frontiers call for research “Spirituality in the Workplace”. The findings suggest that the aforementioned factors are in significant positive relationships. Further, the empirical evidence indicate that there is a significant indirect effect by surface acting on cognitive weariness through job stress. In addition, results reveals that there is a buffering effect by sense of community on surfacing acting and job stress relationship, while there is no significant moderation effect regarding job stress and cognitive weariness association. The findings of this research provide theoretical and practical implications within the scope of spirituality in the workplace.